Immersion and distancing during assimilation of problematic experiences in a good-outcome case of emotion-focused therapy. (4th March 2018) - Barbosa, Eunice; Couto, Ana Bela; Basto, Isabel; Stiles, William B.; Pinto-Gouveia, José; Salgado, João
Abstract: Objective: Some studies have suggested that a decrease in immersion (egocentric perspective on personal experiences) and an increase in distancing (observer perspective on personal experiences) are associated with the resolution of clinical problems and positive outcome in psychotherapy for depression. To help clarify how this change in perspectives relates to clinical change, the present study compared changes in immersion and distancing across therapy with progress in one client's assimilation of her problematic experiences.Method: We analyzed all passages referring to the central problematic experience in a good-outcome case of emotion-focused therapy for depression using the Measure of Immersion and Distancing Speech and the Assimilation of Problematic Experiences Scale.Results: Results showed that immersion and distancing were associated with different stages of assimilation. Immersion was associated with stages of emerging awareness and clarification of the problem and in the application of new understandings to daily life. Distancing was associated with problem-solving and attaining insight.Conclusion: The decrease of immersion and increase of distancing associated with therapeutic improvement should not be taken as a recommendation to avoid immersion and encourage distancing. Immersion and distancing may work as coordinated aspects of the processes of psychotherapeutic change.